IMPACT OF CHANGE ORDERS ON ROAD CONSTRUCTION PROJECT: CONSULTANS’ PERSPECTIVE - Waty, Mega; Sulistio, Hendrik (Journal of Applied Engineering Science, 2022)
Change orders in construction projects have a significant negative impact on project performance. This study aims to determine the impact of change orders in terms of cost, quality, time, organization, and other factors in road construction projects. This was achieved through the distribution of questionnaires and the return of 30 consultant respondents engaged in road construction projects from the provinces of DKI Jakarta, Banten, and West Java. After that, the data obtained is processed using a statistical tool known as Smart PLS. Data processing with Smart PLS tested the validity and reliability and the relationship between variables. There are 6 variables, namely X1, X2, X3, X4, X5, and Y with each indicator, with a total of 17 indicators from X1 to X5 and a total of 4 indicators for Y indicators. The results of this study resulted in the impact of change orders significantly affecting cost (X1), quality (X2), time (X3), organization (X4), and others (5) on road construction projects, the biggest impact being others. The results also show three significant indicators, change orders reduce labor productivity (X5.2), change orders cause disputes in projects (X4.1), and change order to reduce the quality of work ( X2.2)
Keywords: impact of change orders, road construction projects, consultant respondents